Deletion of Ovarian Hormones Induces a Sickness Behavior in Rats Comparable to the Effect of Lipopolysaccharide - Hamid Azizi-Malekabadi; Mahmoud Hosseini; Masoume Pourganji; Hoda Zabihi; Mohsen Saeedjalali; Akbar Anaeigoudari (Neurology Research International)
Neuroimmune factors have been proposed as the contributors to the pathogenesis of sickness behaviors. The effects of female gonadal hormones on both neuroinflammation and depression have also been well considered. In the present study, the capability of deletion of ovarian hormones to induce sickness-like behaviors in rats was compared with the effect lipopolysaccharide (LPS). The groups were including Sham, OVX, Sham-LPS, and OVX-LPS. The Sham-LPS and OVX-LPS groups were treated with LPS (250 μg/kg) two hours before conducting the behavioral tests. In the forced swimming (FST), the immobility times in both OVX and Sham-LPS groups were higher than that of Sham (P<0.001). In open-field (OP) test, the central crossing number by OVX and Sham-LPS groups were lower than Sham (P<0.001) while there were no significant differences between OVX-LPS and OVX groups. In elevated plus maze (EPM), the percent of entries to the open arm by both OVX and Sham-LPS groups was lower than that of Sham group (P<0.001). The results of present study showed that deletion of ovarian hormones induced sickness behaviors in rats which were comparable to the effects of LPS. Moreover, further investigations are required in order to better understand the mechanism(s) involved.